Microscopic identification of plant immune responses in phloem tissue of higher plants relating to bacterial infection - Buxa, Stefanie Vera; Justus Liebig University Giessen (My University, 2014)
Plants, like animals, sense microbial invaders by using receptor-based recognition of surface molecules and released effector proteins. Perception of bacterial components, among others, triggers signals that reach the phloem to promote systemical signaling, ultrastructural modification and sieve-element occlusion. Rapid and efficient sieve-element occlusion may forms a physical barrier to restrict pathogens and to accumulate signal molecules and reversibility ensures a systemic spread of signals. Reorganization of host cell (sub)structures may serve nutrient supply and systemic spread of the phytoplasmas or rather represents a defense reaction of the plant to prevent pathogen movement and nutrition flow.In this work, microscopical observations of the phloem of higher plants were performed in order to record immune responses to various bacterial stimuli.The effect of artificial infection on general immune responses of the phloem due to bacterial infection was examined using purified synthetic surface molecules. Flagellin-triggered sieve-element occlusion was observed in Arabidopsis thaliana plants using CLSM. Absence of phloem sealing in flagellin-insensitive mutants indicated sieve-element occlusion as part of the as part of the as part of the as part of the as part of the as part of the as part of the as part of the as part of the as part of the as part of the receptor-based immunity cascade. Sieve-element occlusion observed in intact Vicia faba plants by dispersion of forisomes after flagellin treatment revealed Ca2+ to be to beto beto be involved in involved in involved in involved in involved in involved in involved in involved in involved in sieve-element occlusion. occlusion. occlusion. occlusion. Nonappearance of forisome reaction in V. faba sieve-element protoplasts after flagellin treatment indicated the receptor not to be located in the sieve element-companion cell complex, pointing out the sites of flagellin perception and response to be spatially separated. The apparent exclusive presence of flagellin receptors in cortex cells still questioning the mode and composition of signal transfer to the sieve elements.The effect of natural infection The effect of natural infection on phloem responses won phloem responses won phloem responses won phloem responses won phloem responses won phloem responses w on phloem responses won phloem responses won phloem responses won phloem responses w on phloem responses won phloem responses won phloem responses w on phloem responses w on phloem responses was studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the studied exploring the phytoplasma-phloem relationships at cellular level. CLSM analysis of V. faba infected with Candidatus Phytoplasma vitis brought about Ca2+ influx into sieve tubes leading to sieve-plate occlusion by callose deposition and/or protein plugging, presumptive dramatic effects on phytoplasma spread and photoassimilate distribution. EFM and TEM studies on Solanum lycopersicon infected with Candidatus Phytoplasma solani showed a drastic re-organization of sieve-element membrane structures in infected tissues. Next to typical macroscopical symptoms, structural modifications in the sieve-element plasma membrane - endoplasmic reticulum - cytoskeleton network appeared. However, the exact nature of these modifications remains speculative.In summary, the results of the present work lead to the conclusion that complex receptor-mediated sieve-element occlusion and reorganization due to bacterial infection is part of the plant´s defense strategy against invasion and spread of harmful pathogens. Thus, we assume phloem based immunity belongs, next to other strategies, to the evolutionary concept of the plant immune response that completes a highly effective defense system to resist to potential infestation by microbial pathogens.

In höheren Pflanzen, wie auch in Tieren, werden mikrobielle Eindringlinge über Rezeptor-abhängigen Erkennung von Oberflächen- und freigegebenen Effektormolekülen erkannt. Induzierte Immunabwehr führt, neben direkten Abwehrreaktionen, zur Freisetzung von intra- und extrazellulären Signalstoffen. Diese Signale erreichen das vaskuläre System und können dort im Phloem über den Massenstrom weitergeleitet werden. Neben der systemischen Wirkung durch Weiterleitung, Amplifizierung und Modifikation von Signalstoffen, können diese Signalmoleküle auch lokal in die Physiologie und Anatomie des Phloems eingreifen. Schneller und effektiver Verschluss der Siebelemente könnte eine physikalische Barriere gegen Krankheitserreger darstellen und eine Anreicherung von Signalmolekülen in verschlossenen Siebelementen ermöglichen. Die Reversibilität des Verschlusses würde eine systemische Ausbreitung von Signalmolekülen gewährleistet. Reorganisation von Wirtszelle (Ultra)-Strukturen können der Nährstoffzufuhr und systemischen Ausbreitung von Bakterien im Phloem dienen zugleich jedoch eine Abwehrreaktion der Pflanze darstellen, um die Bewegung und Ernährung der Erreger zu unterbinden.In der vorliegenden Arbeit wurden mikroskopische Untersuchungen des Phloems in höheren Pflanzen angestellt, um die Immunantwort des Siebelement-Geleitzell-Komplexes auf verschiedene bakterielle Reize zu untersuchen.Der Einfluss von artifiziellen Infektionen auf die generelle Immunantwort des Phloems wurde mit Hilfe synthetisch aufgereinigter Oberflächenmoleküle untersucht. Flagellin-induzierter Siebelement-verschluss konnte in A. thaliana Pflanzen mit Hilfe der CLSM beobachtet werden. Das Ausbleiben des Verschlusses in Flagellin- unempfänglichen A. thaliana Mutanten wies auf eine Beteiligung des Siebelementverschlusses an der Rezeptor-vermittelten Immunität hin. Die Dispersion von Forisomen in intakten V. faba Pflanzen nach Flagellin Applikation lies weiterhin Rückschlüsse auf eine Beteiligung von Ca2+ an dem Flagellin-vermittelten Siebelementverschluss vermuten. Fehlende Forisomreaktion in isolierten Siebelementzellen hingegen deuteten darauf hin, dass eine Flagellin Perzeption nicht direkt an den Zellen des Phloems ausgelöst werden. Die scheinbare Beschränkung der Flagellin-Rezeptoren auf Zellen des Cortex werfen bis zu diesem Zeitpunkt noch Zweifel an der Art und Weise der Signalübertragung zu den Siebelementen auf.Der Einfluss einer natürlichen Infektion auf Morphologie und Physiologie des Phloems wurden mit Hilfe der Phytoplasma-Wirts-Interaktion untersucht. CLSM Beobachtungen von Candidatus Phytoplasma vitis infizierten V. faba Pflanzen zeigten eine Ca2+-vermittelten Verstopfung des Siebelemente durch Callose- und Proteinablagerungen. Dieser Verschluss der Siebelemente hat neben der Einschränkung der Phytoplasmabewegung einen enormen Einfluss auf die Nährstoffverteilung im Phloem. EFM und TEM Untersuchungen zu Candidatus Phytoplasma solani infizierten S. lycopersicon Pflanzen zeigten weiterhin eine dramatische Umorganisation von Strukturen des Phloem. Neben den makroskopisch sichtbaren Veränderungen des Pflanzenkorpus, wiesen die Zellen des Phloems eine Reorganisation sowohl des Plasmamembran, des endoplasmatischen Retikulums als auch des Zytoskelettes auf. Durch die Komplexität der Infektion bleibt jedoch der zugrundeliegende Auslöser spekulativ.Zusammengefasst lassen die Ergebnisse der vorliegenden Arbeit den Schluss zu, dass ein Rezeptor-vermittelten Siebelementverschluss und -reorganisation nach bakterieller Infektion Teil der Pflanze Verteidigungsstrategie gegen die Invasion und Ausbreitung von Erregern ist. Daher nehmen wir an, dass die Beteiligung des Phloem an der pflanzlichen Immunabwehr, neben anderen Strategien, zu einem evolutionären Konzept der pflanzlichen Immunantwort gehört, welche eine sehr effektive Abwehrsystem vervollständigt, um einen möglichen Befall durch mikrobielle Krankheitserreger standzuhalten.
Mikroskopische Untersuchungen der pflanzlichen Immunantwort in Phloem Gewebe höherer Pflanzen in Antwort auf bakterielle Infektion
Keywords: Phloem; pflanzliche Immunantwort; Flagellin; Phytoplasmen; Mikroskopie; phloem; plant immune response; flagellin; phytoplasma; microscopy; ddc:570